Meta-Analysis the Effect of Pharmaceutical Care on Blood Glucose Level in Type 2 Diabetes Mellitus Patients - Syafira, Muthia; Rahardjo, Setyo Sri; Murti, Bhisma (Journal of Health Policy and Management, 2022)
Background: Pharmaceutical care is a patientoriented program carried out by pharmacists. In the management of type 2 diabetes mellitus (T2DM) several parameters have been determined as targets for the success of pharmaceutical care such as HbA1c and the level of patient compliance. This paper aims to evaluate the role of pharmaceutical care in improving clinical outcomes and compliance of patients with T2DM.Subjects and Method: This study was conducted using a Systematic Review and Metaanalysis study design using PICO, population: Diabetes mellitus type 2 patients, Intervention: Obtaining pharmaceutical care. Comparison: Did not receive pharmaceutical care, Outcome: Hba1c. The articles used in this study came from 4 databases, namely Pubmed, ScienceDirect, ProQuest and Google scholar. Article keywords are Diabetes Mellitus, Type 2 OR T2DM OR Type 2 diabetes AND Pharmaceutical care OR Clinical pharmacy OR Community pharmacy OR Pharmacist* OR Pharmaceutical services OR Education OR Intervention OR Medication Management AND Knowledge OR adherence OR HbA1c OR glycemic control” Included articles in this study is a full paper article, RCT study design for 20112021.Results: A total of 12 RCT studies with 1,746 T2DM patients in Asia (Jordan, Hong Kong, Northern Cyprus, Thailand, China, Malaysia and Indonesia), Americas (Brazil) and Europe (France and England). From the data processing, it was found that the provision of pharmaceutical care reduced HbA1c levels by 0.81 in patients with type 2 diabetes mellitus compared to those without pharmaceutical care. (SMD= 0.81; 95% CI= 1.11 to 0.52 p<0.0001).Conclusion: The provision of pharmaceutical care can improve clinical outcomes in the form of decreasing HbA1c values.Keywords: Pharmaceutical Care, Type 2 Diabetes Mellitus, HbA1c, Glycemic Control.Correspondence: Muthia Syafira. Masters Program in Public Health Sciences, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email mutsyaf@student.ac.id. Mobile: +6285920660180.Journal of Health Policy and Management, (2022), 07(02): 112-124https://doi.org/10.26911/thejhpm.2022.07.02.03